Using mimicking gestures to improve observational learning from instructional videos. Issue 5 (27th May 2020) - Mierowsky, Ruth; Marcus, Nadine; Ayres, Paul
Abstract: This study, generated from considerations of embodied cognition, observational learning, and cognitive load theory, investigated the effect of mimicking gestures on learning to play piano tasks. Fifty university students from an Australian University, with two different levels of piano-playing experience, were randomly assigned to one of the two different gesturing conditions in a 2 (gestures vs. no-gestures) × 2 (novice vs. more expertise) design. All groups viewed an animated video presentation of four musical scores being played on a piano with the hand motions visible, accompanied by the sounds of the notes played. Participants in the gesturing condition were required to gesture while watching the presentations, but in the no-gesturing condition, gesturing was prohibited. Test results indicated a significant learning advantage to gesturing with reduced cognitive load. It was also evident that the efficacy of gesturing was influenced by learner expertise and task complexity.